Need for research in health systems and services: regarding the use of clinical practice guidelines - Luis Alberto Corona Martínez (Medisur, 2020)
This article aims at drawing attention to the current contradiction between the importance and need for research in health systems and services and the scarce execution of these works. A group of interconnected elements is exposed, which may be related to this negative phenomenon. Meanwhile precision and accuracy of its results, when obtained under real life conditions, are highlighted as strength of this research. It is stated how the use of clinical practice guidelines in health care constitutes an evident opportunity to increase research in health systems and services.